2010
DOI: 10.1007/s11747-010-0192-7
|View full text |Cite
|
Sign up to set email alerts
|

An examination of consumer sentiment toward offshored services

Abstract: This research identifies and analyzes the underlying elements and consequences of consumer sentiment toward offshored services. This is accomplished by initially conceptualizing consumer sentiment toward offshored services, then developing and validating a multidimensional scale (OFFSERVSENT) to measure the construct. This research determines that consumer sentiment toward offshored services is instrumental in explaining consumers' commitment to and global attitudes toward firms that offshore services as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 71 publications
0
54
0
1
Order By: Relevance
“…Empirical research has shown that outsourcing and offshoring can produce business benefits if client organizations build sourcing capabilities and enact management practices (e.g., Carmel & Tjia, 2005;Choudhury & Sabherwal, 2003). Beyond this economic/managerial view of sourcing are the political and social views that influence sourcing decisions (e.g., Thelen et al, 2010;Heeks & Arun, 2010). Citizens want companies to keep good jobs in their respective domestic borders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical research has shown that outsourcing and offshoring can produce business benefits if client organizations build sourcing capabilities and enact management practices (e.g., Carmel & Tjia, 2005;Choudhury & Sabherwal, 2003). Beyond this economic/managerial view of sourcing are the political and social views that influence sourcing decisions (e.g., Thelen et al, 2010;Heeks & Arun, 2010). Citizens want companies to keep good jobs in their respective domestic borders.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some research has also highlighted the broader negative sentiments against offshoring business services (just as with offshoring manufacturing) and various institutional attempts at prodding organizations to stop offshoring business services in the interest of domestic jobs (e.g., Shao & David, 2007;Thelen, Yoo, & Magnini, 2010;Khan & Lacity, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They suggest that while migrating call service centers to offshore locations may be an acceptable strategy for well-known firms, less well-known firms should exercise greater caution in pursuing such a course of action. Summarizing prior research on the topic, Thelen et al (2011) note that front-office offshoring has been found to negatively impact perceived service quality, customer satisfaction and customer loyalty. Although it is conceivable that CRM outsourcing can enhance a business' customer relationship performance as a result of the specialized CRM skills and infrastructure of third-party vendors, the preponderance of arguments suggest a negative relationship between CRM offshore outsourcing intensity and customer relationship performance.…”
Section: Consequences Of Crm Offshore Outsourcing Intensitymentioning
confidence: 94%
“…Demand-side effects refer to the impact of CRM offshore outsourcing on a firm's customers. For instance, Thelen et al (2011) report that offshoring of front office CRM processes negatively impacts perceived service quality, customer satisfaction and customer loyalty. In effect, besides impacting production costs and transaction costs, CRM offshore outsourcing can also potentially impact the quality of service delivery and customer satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Although this trend has been the subject of debate in academic journals in the past years, many of its features are still not clear (Kenney et al 2009), and there is a continued demand for empirical evidence and greater theoretical rigor (Bunyaratavej et al 2011). Offshoring is often described in the academic literature as an efficiency-seeking international strategy, in recent years also as a (human) resource-seeking strategy, and offshoring and global sourcing strategies have frequent linkages with marketing and foreign market access strategies (Kotabe 1992(Kotabe , 2001Kotabe et al 2009;Kotabe and Murray 2004), as well as consumer sentiments (Thelen et al 2011).…”
Section: Introductionmentioning
confidence: 99%